Seroprevalence of Baylisascaris procyonis Infection among Humans, Santa Barbara County, California, USA, 2014–2016 - Weinstein, Sara B. (Emerg Infect Dis, 2017)
Baylisascaris procyonis (raccoon roundworm) infection is common in raccoons and can cause devastating pathology in other animals, including humans. Limited information is available on the frequency of asymptomatic human infection. We tested 150 adults from California, USA, for B. procyonis antibodies; 11 were seropositive, suggesting that subclinical infection does occur.